Study on the Experimental of the Influence of Lubricant Viscosity on Transmission Efficiency of Rear Axle and Vehicle Fuel Consumption - Liu Chuanbo; Dong Tuo; Mo Yimin; Zhou Wenjun; Wang Junping (Jixie chuandong)
As the national policy encourage to reduce the fuel consumption and oil prices rising gradually,to reduce fuel consumption of the vehicle is widely concerned.The fuel consumption is closely related to the transmission efficiency,and the rear axle plays an important role in auto transmission system and different lubricant has a great influence on the transmission efficiency of rear axle,the viscosity of the lubricant,the losses of gear meshing and churning losses are analyzed,a lot of experiments are conducted to investigate the influence of viscosity of lubricant on transmission efficiency of rear axle.It is found that relatively low viscosity lubricant contributes to improving the transmission efficiency of rear axle and makes an important significance on reducing vehicle fuel consumption.